KOLABORASI PEMERINTAH DESA DAN TOKOH ADAT DALAM PELESTARIAN RIMBO LARANGAN DESA SEBERANG TERATAK AIR HITAM KECAMATAN SENTAJO RAYA TAHUN 2018-2019 - Sukri Afriadi; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Identification of Problems in Collaborative Research with village government and traditional leaders in preserving Rimbo Larangan, Seberang Teratak Air Hitam Village, Sentajo Raya District 2018-2019, namely the fading of meetings held by traditional institutions in carrying out activities in efforts to preserve the forbidden jungle, the status of prohibited forest which is still recorded as APL (Other Use Area) making it difficult to manage or transfer the function of area utilization, the lack of the role of the Regional Government in efforts to preserve the prohibition forest. This study uses a qualitative research method that describes the data obtained through interviews and documentation. While the data source used is primary data obtained directly from the research location in the form of information submitted by informants, and supported by secondary data, namely documents related to research. The results of the collaboration of the village government and traditional leaders in the preservation of Rimbo Larangan Seberang Village of Teratak Air Hitam, Sentajo Raya District 2018-2019, are that in terms of formal agreements and missions there is no formal agreement but, the agreement agreed upon by all parties that Rimbo Larangan Seberang Teratak Air Hitam Village is a customary forest managed by traditional institutions and the people of Seberang Teratak Air Hitam Village. Besides that, in terms of leadership that the Customary Institution holds authority and leadership in the preservation of Rimbo Larangan, then in terms of legitimacy there is no Written Regulation regarding the management of the Rimbo Larangan area, as for law enforcement and management regulations still use the applicable Customary Law. Keywords: Collaboration, Preservation, Rimbo Larangan